Tracking of sports practice from childhood to adolescence and its associations in a school-based study - Tebar, William [UNESP]; Fernandes, Romulo [UNESP]; Zanuto, Edner [UNESP]; Gil, Fernanda [UNESP]; Delfino, Leandro [UNESP]; Scarabottolo, Catarina [UNESP]; Ronque, Enio Vaz; Christofaro, Diego [UNESP] (My University, 2019)
Objective: To analyze the tracking of sports practice and its associations in adolescents. Methods: A randomized scholar sample of 870 adolescents between 10-17 years was assessed. Tracking of sports practice from childhood to adolescence was assessed by questionnaire such as ethnicity socioeconomic status and parental education level. Associations between variables were analyzed by chi-square test and its magnitude by binary logistic regression. Results: Tracking of sports practice was 48.8%. Boys were about twice likely to tracking sports practice than girls. Older adolescents were 33% less likely to tracking than younger. Black / brown adolescents were respectively 67% and 33% less likely to tracking sports practice than white. Adolescents with low-middle socioeconomic levels and low education of mother were less likely to tracking sports practice than their counterparts. Soccer was most sport practiced in childhood (29.3%) and adolescents who practiced team sports were more likely to maintain the sports practice from childhood to adolescence than those who practiced individual sports. Conclusion: Tracking of sports practice was associated with sex age ethnicity socioeconomic level parental education and sport modality.
Keywords: Adolescents; Children; Ethnicity; Physical activity; Students